Effects of asbestos and smoking on the levels and rates of change of lung function in a crocidolite exposed cohort in Western Australia. Issue 12 (24th November 2004) - Alfonso, H S; Fritschi, L; de Klerk, N H; Olsen, N; Sleith, J; Musk, A W
Abstract : Background: Increased rates of death from asbestos related diseases have been reported in former workers and residents exposed to crocidolite (blue asbestos) at Wittenoom, Western Australia. Exposure to asbestos is associated with reduced static lung volumes, gas transfer and lung compliance, and a restrictive ventilatory abnormality. Methods: The effects of crocidolite exposure and smoking history on levels and rates of change of lung function were evaluated using a linear mixed model. Lung function was measured as forced expiratory volume in 1 second (FEV1 ), forced vital capacity (FVC), and FEV1 /FVC. Results: Cumulative doses of asbestos and the presence of radiographic asbestosis were associated with lower levels of FEV1 and FVC and a steeper decline during the period of observation. Subjects exposed to asbestos at a younger age had lower levels of FEV1 and FVC. Current smokers had lower levels and a steeper decline in lung function than never smokers. No significant interactions between crocidolite exposure and smoking on the levels or rates of change of lung function were found. Conclusions: The deleterious effects of crocidolite exposure on lung function persist in this population, despite asbestos exposure having ceased more than 30 years ago. No significant interactions were found in this population between asbestos and smoking at the first visit or longitudinally.